THE IMPACT OF PARENTAL DIVORCE ON THE SOCIO-EMOTIONAL DEVELOPMENT OF EARLY CHILDHOOD IN MOYOT HALL, MOYOT VILLAGE, SAKRA DISTRICT, EAST LOMBOK REGENCY - Zikriatul Isnaini (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study found that many children are victims of parental divorce which has an impact on the social and emotional well-being of early childhood children, this causes children to be neglected and even children are less able to concentrate on their studies, even as a result of their parents' divorce, children sometimes appear gloomy, some are also a bit naughty due to a lack of attention from their parents which has an impact on social and emotional well-being. Therefore, the researcher is interested in conducting a study entitled: "The Impact of Parental Divorce on the Social and Emotional Development of Early Childhood Children in Moyot Hamlet, Moyot Village, Sakra District, East Lombok Regency." The research used a descriptive qualitative approach. The objects of this study were early childhood divorce victims living in Moyot Hamlet, Moyot Village, Sakra District, East Lombok Regency. The subjects of this study were the parents and the village head of Moyot. The data collection methods used were observation, interviews, and documentation. The results of this study revealed various impacts of parental divorce on the social and emotional development of early childhood, namely: 1) fear, shame, worry, anxiety, anger, jealousy, grief, curiosity, and joy. 2) efforts made by parents towards the social and emotional development of early childhood, namely parents as the best caregivers for their children, as the first madrasah for their children, and teaching their children to behave politely and be able to Becoming a pious and righteous child.